2017
DOI: 10.1162/neco_a_00935
|View full text |Cite
|
Sign up to set email alerts
|

Multisensory Bayesian Inference Depends on Synapse Maturation during Training: Theoretical Analysis and Neural Modeling Implementation

Abstract: Recent theoretical and experimental studies suggest that in multisensory conditions, the brain performs a near-optimal Bayesian estimate of external events, giving more weight to the more reliable stimuli. However, the neural mechanisms responsible for this behavior, and its progressive maturation in a multisensory environment, are still insufficiently understood. The aim of this letter is to analyze this problem with a neural network model of audiovisual integration, based on probabilistic population coding-t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
46
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(47 citation statements)
references
References 56 publications
1
46
0
Order By: Relevance
“…In a previous paper (Ursino et al, 2017) we demonstrated that the width of the RFs reflects the likelihood of the inputs. As a new element, the position of the RFs reflects the prior about the frequency of the inputs (in particular, the greater probability to have a visual stimulus close to the fovea, according to Equation 10).…”
Section: Resultsmentioning
confidence: 74%
See 4 more Smart Citations
“…In a previous paper (Ursino et al, 2017) we demonstrated that the width of the RFs reflects the likelihood of the inputs. As a new element, the position of the RFs reflects the prior about the frequency of the inputs (in particular, the greater probability to have a visual stimulus close to the fovea, according to Equation 10).…”
Section: Resultsmentioning
confidence: 74%
“…In fact, according to this rule, each receptive field after training becomes equal to its average sensory input (Ursino et al, 2017). Since we assumed that the receptive fields are initially much larger than the inputs, training necessarily results in a progressive reduction of the RF width.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations